Seroprevalence of antibodies against hepatitis A and E among the general population in 5 provinces, Lao People’s Democratic Republic: Variation according to location - Vilaysone Khounvisith; Siriphone Virachith; Nouna Innoula; Latdavone Khenkha; Bounta Vongphachanh; Jan Hattendoft; Peter Odermatt; Judith M Hübschen; Antony P Black (PLoS ONE, 2025)
Hepatitis A and E viruses (HAV and HEV) are transmitted through the faecal-oral route: via contaminated food, water, and contact with infected people and/or animals for HEV. Due to limited data from Lao People’s Democratic Republic (Lao PDR), we assessed HAV and HEV seroprevalence in the Lao general population. A cross-sectional study collected 2412 serum samples and demographic information from participants (5–93 years) across five provinces. Anti-HAV (IgM and IgG) and anti-HEV antibodies (IgG) were detected by enzyme-linked immunosorbent assay (Dia.Pro). The overall seroprevalence of anti-HAV was 84.3% and anti-HEV was 57.9%. Seropositivity was associated with occupation, location, increasing age, ethnicity (only for anti-HAV) and sex (only for anti-HEV). The age at which 50% of the population was seropositive differed from 12 years (Oudomxay) to 26 years (Savannakhet and Vientiane) for anti-HAV and from 22 years (Savannakhet) to 49 years (Vientiane) for anti-HEV. The prevalence of double seropositivity was high overall (53.4%), particularly in Savannakhet and Champasack. These significant differences according to location and socio-demographics may be the result of variation of exposure to the viruses, such as through water, sanitation and hygiene-related risks, occupational exposure and animal contact. Further studies are warranted to identify the most important risks for transmission in Lao PDR in order to develop targeted public health interventions.